TQM, SISTEM PENGHARGAAN DAN SISTEM PENGUKURAN KINERJA SEBAGAI FAKTOR KINERJA KARYAWAN PT. SAKTI INDONESIA SERTIFIKASI - Wasis Swo Leksana; Moh. Bukhori; Widi Dewi Ruspitasari (Unitri Press, 2021)
This study aims to examine Total Quality Management, reward systems, and performance measurement systems as factor on the performance of employees of PT. Sakti Indonesia Certification. Using quantitative with questionnaire to be analyzed by multiple linear regression. The results showed that all factor has positive impact but TQM and measurement systems has not significant effect while the reward system has significant effect on employees performance. For future can expand the scope of research, so that researchers' results are more likely to be concluded in general. And also in order to use research objects other than service companies that have more samples